The BRD trilogy [videorecording (DVD)] : Rainer Werner Fassbinder's The marriage of Maria Braun, Veronika Voss, Lola - Fassbinder, Rainer Werner, 1945-1982; Schygulla, Hanna, 1943-; Zech, Rosel, 1942-2011; Sukowa, Barbara, 1950- (Criterion collection, 2003)
In 1978 Rainer Werner Fassbinder embarked upon a project to trace the history of postwar Germany in a series of films told through the eyes of 3 remarkable women. The 3 films would garner him the international acclaim for which he had always yearned and place his name foremost in the canon of New German Cinema.